2020
DOI: 10.1021/acsomega.0c03560
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium-Based Ionic Liquids as Clay Swelling Inhibitors: Mechanism, Performance Evaluation, and Effect of Different Anions

Abstract: Clay swelling is one of the challenges faced by the oil industry. Water-based drilling fluids (WBDF) are commonly used in drilling operations. The selection of WBDF depends on its performance to improve rheology, hydration properties, and fluid loss control. However, WBDF may result in clay swelling in shale formations during drilling. In this work, the impact of imidazolium-based ionic liquids on the clay swelling was investigated. The studied ionic liquids have a common cation group, 1-allyl-3-methyllimidozi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…The filtrate fluid's charge and electrolytic properties can be efficiently controlled by the clay stabilizers and the clay platelets can be held in place. Imidazolium-based ionic liquids have been identified as a possible inhibitor of clay swelling and research in this area is progressing at a brisk pace [21]. Shale oil is the unconventional oil extracted from a class of fine-grained classic sedimentary rocks known as shale rocks.…”
Section: Crude Oil Industrymentioning
confidence: 99%
“…The filtrate fluid's charge and electrolytic properties can be efficiently controlled by the clay stabilizers and the clay platelets can be held in place. Imidazolium-based ionic liquids have been identified as a possible inhibitor of clay swelling and research in this area is progressing at a brisk pace [21]. Shale oil is the unconventional oil extracted from a class of fine-grained classic sedimentary rocks known as shale rocks.…”
Section: Crude Oil Industrymentioning
confidence: 99%
“…ILs have gained a lot of attention in the last few decades because of interesting characteristics, such as low vapor pressure, specific solvating ability, high thermal stability, compatibility with inorganic, organic, and polymeric materials, and so forth. , Because of excellent characteristics, ILs have found many industrial applications, including nanocomposite preparation, dye adsorption, catalysis, gas separation, green solvents, and so forth. − In recent years, ILs have been employed for many oil and gas applications. Numerous researchers have studied the use of ILs in drilling/completion fluids and enhanced oil recovery (EOR). − …”
Section: Introductionmentioning
confidence: 99%
“…These segments of the ILs have distinguished effects on clay swelling inhibition mechanisms. Ahmed Khan et al (2020) studied the effects of halogen group anions and reported that there is negligible difference in their inhibition performances due to different halides (Ahmed Khan et al 2020). The reason behind these similar inhibition performances is that these anions possess almost similar types of molecular properties.…”
Section: Introductionmentioning
confidence: 99%